The Octet Rule Revisited: A Quantum-Continuum Framework for Chemical Bonding - Barack Ndenga (Publisher, 2025)
The octet rule is ubiquitously taught as a universal principle of chemical stability, yet it is fundamentally a pedagogical approximation that breaks down across vast regions of chemical space. Hypervalent molecules (e.g., SF₆, PCl₅), electron-deficient systems (e.g., BF₃), transition-metal complexes, and metallic clusters all violate the rule in systematic and predictable ways. Despite this, no unified framework has reconciled these deviations with the underlying quantum-mechanical continuum of electronic interactions. Here, we propose a fully modern quantum-continuum interpretation of chemical bonding based on electron-density topology, multi-center bonding models, and the interplay between orbital energetics and electron correlation. This framework demonstrates that “octet violations’’ are not anomalies but natural consequences of delocalization, symmetry, and energy minimization in many-electron systems. By replacing the rigid octet paradigm with a continuous, energy-driven model, we resolve the apparent contradictions between introductory rules and real chemical behavior. Keywords Octet rule; hypervalent molecules; electron deficiency; quantum continuum model; QTAIM; ELF; multi-center bonding; chemical bonding theory.
This work presents a modern, quantum-continuum reinterpretation of chemical bonding, demonstrating that the octet rule is a limited pedagogical approximation rather than a universal principle. Using electron-density topology, multi-center bonding theory, and quantum-mechanical energy decomposition, this article unifies the behavior of electron-deficient compounds, hypervalent molecules, and metallic systems into a single continuous framework. The model resolves the long-standing contradiction between textbook rules and real molecular behavior, offering a coherent and up-to-date foundation for chemical bonding theory.